ENVISAGING CODE-MIXING AND CODE-SWITCHING IN ENGLISH CONVERSATION AMONG THAI STUDENTS: BREACHING THE MOTIVES FROM SOCIOLINGUISTIC PERSPECTIVES - Ikrar Genidal Riadil; Nattakan Dilts (Sanata Dharma University, 2022)
People always communicate to make relationships with others. Some way they do this is to make the other understand what the speaker means. Therefore, the speaker uses code-mixing and code-switching to make the listener understand. The purpose of code-mixing and code-switching is to make the utterance more communicative, and more friendly to show the master can speak more than two languages. In this research, the subject is students from the English Department at Tidar University in Indonesia and the International Business China Program Faculty of International Studies at Prince of Songkla University in Thailand. This research used a descriptive qualitative method in which the researchers describe the form, the types, and the reason for code-mixing and code-switching in an educational conversation by students from the English Department Tidar University in Indonesia and International Business China Program Faculty of International Studies Prince of Songkla University in Thailand. All of the students in daily life use code-mixing and code-switching to communicate with others or their lecturers because they are from the English Department and International Program where all of the lectures are taught in English. The types of code mixing such as insertion, alternation, and congruent lexicalization based on Singh and Sachan (2017), while types of code-switching are intra-sentential, inter-sentential, and tag switching based on Ansar (2017). The researchers also found some factors related to Hudson (1980) such as social factors, cultural factors, and individual factors. In a nutshell, as stated from the data analysis, numerous code-mixing and code-switching used by these students in their daily life, it helps them to understand and simplify communication.